Pengaruh Marketing Mix Dan Social Media Terhadap Keputusan Pembelian Frozen Food Di Kota Makassar Menggunakan Pendekatan Technology Acceptance Model Dan Stimulus-Organism-Response - Gosal, Brandon; Fouzia, Nury; Djuranovik, Evelyn; Wijaya, Wendy; Monalisa, Monalisa (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2025)
This study aims to analyze the effect of marketing mix and social media on purchasingdecisions for frozen food products in Makassar City. This research uses the TechnologyAcceptance Model (TAM) and Stimulus-Organism-Response ( SOR ) frameworks, to analyzehow the Marketing Mix and Social Media play a role in Purchasing Decisions in the context ofpurchasing frozen food. The research sample involved 206 consumers who had purchasedfrozen food products, where data was collected through a survey using a questionnaireinstrument. The data analysis technique was carried out using the Partial Least Square -Structural Equation Modeling (PLS-SEM) approach through WarpPLS version 8.0 software,to identify the significant influence of each variable on purchasing decisions. The resultsshowed that Marketing Mix and social media had a significant effect in influencing purchasingdecisions. This research shows the importance of using social media by combining themarketing mix to increase trust and brand images, and expand market share. This strategyallows frozen food companies and similar businesses to be more effective in influencingconsumer purchasing decisions in the digital age.